PENGARUH MODEL MIND MAPPING TERHADAP KETERAMPILAN MENULIS DESKRIPSI KELAS IV SD - Darmawangsa, Adam; Satrio Wibowo; Galuh Kartika Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research was motivated by an evaluation of the improvement in descriptive writing skills of fourth grade students at Katerungan Krian Elementary School using the Mind Mapping model. This research was conducted to improve the descriptive writing skills of fourth grade elementary school students and evaluate student responses after using the Mind Mapping model to learn descriptive writing skills. This research uses quantitative research methods such as quasi-experimental research (Quasi Experimental Design). The data collection method uses the Student Learning Outcomes Test to measure students' ability to write descriptions. And a questionnaire on student responses to the mind mapping model for descriptive writing skills. Analysis of research results shows that test scores related to student learning outcomes in the experimental class ranged from 70 to 93, with a pretest average of 82.9. Meanwhile, the control class had scores ranging from 67 to 90 with a pretest average of 76.45. The results of the questionnaire showed that students gave an average rating of 88% to the Mind Mapping model which was considered very good.